Vermont Marble Company, Proctor, Vermont: Otter Creek hydroelectric feasibility report (International Engineering Co., Inc., San Francisco, CA (USA), 1979)
Vermont Marble Company (VMCO) owns and operates four hydroelectric projects in a 50-mile reach of Otter Creek in west central Vermont. This study concerns three of the installations - Center Rutland, Beldens, and Huntington Falls. The fourth site is known as Proctor and will be studied separately. All four plants operate as run-of-river stations, and the limited reservoir storage capacity places severe limitations on any other type of operation. The plants are presently operating at much lower outputs than can be obtained, because they do not use the available discharge and head. The results show that, under the assumptions made in this study, Beldens and Huntington Falls can be economically improved. The rehabilitation of the Center Rutland plant did not look economically attractive. However, the improvement of Center Rutland should not be eliminated from further consideration, because it could become economically attractive if the cost of energy starts escalating at a rate of around 10% per year. The study included a brief appraisal of the existing generating facilities and condition of existing concrete structures, a geological reconnaissance of the sites, analysis of the power potential, flood studies, technical and economic investigations and comparative evaluations of the alternatives for developing the streamflow for power generation, selection of the most suitable alternative, financial analysis, preparation of drawings, and preparation of detailed quantity and cost estimates.